The remineralization effectiveness of PAMAM dendrimer with different terminal groups on demineralized dentin in vitro. Issue 87 (1st December 2017) - Tao, Siying; Fan, Menglin; Xu, Hockin H. K.; Li, Jianshu; He, Libang; Zhou, Xuedong; Liang, Kunneng; Li, Jiyao
Abstract : The aim of this study was to examine the dentin remineralization extent that poly(amido amine) (PAMAM) induces quantitatively, and select the most effective kind of PAMAM with a certain terminal group for dentin remineralization, both for the first time. Abstract : The aim of this study was to examine the dentin remineralization extent that poly(amido amine) (PAMAM) induces quantitatively, and select the most effective kind of PAMAM with a certain terminal group for dentin remineralization, both for the first time. Prepared demineralized dentin specimens were divided into four groups: (1) dentin coated with deionized water, (2) dentin coated with PAMAM-OH, (3) dentin coated with PAMAM-COOH, and (4) dentin coated with PAMAM-NH2 . Specimens were then treated with artificial saliva at 37 °C for 28 days. The remineralized dentin specimens were examined by transverse microradiography (TMR), hardness testing, scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). The SEM images were also analyzed with Image-Pro Plus software. The three treatment groups all induced lower mineral loss, lower lesion depth, higher dentin hardness, higher blocking rate of dentin tubules and higher percentages of Ca and P elements than the control group. PAMAM-NH2 or PAMAM-COOH induced lower mineral loss, lower lesion depth and a higher blocking rate of dentin tubules than PAMAM-OH. There was no significant difference between PAMAM-NH2 and PAMAM-COOH with regard to mineral loss, lesion depth, dentin hardness, blocking rate of dentin tubules and percentages of Ca and P elements. In conclusion, PAMAM with different terminal groups could induce dentin remineralization, and PAMAM-NH2 or PAMAM-COOH showed the strongest remineralization capabilities on demineralized dentin.